Innovation in Cleaning Tools: User-Centered Design for Waste Separation Using Design Thinking, the Kano Model, and AHP - Tarazona Mallqui, Nathaly Naomi; Manzanares Grados, Ruth Aracelis (LACCEI, 2025)
Street vending is a key economic activity and an ideal setting for implementing sustainable solutions. This study evaluates the satisfaction of street vendors in Metropolitan Lima who use cleaning tools for waste management in food vending areas. Issues related to transportation, storage, and waste separation were identified, impacting hygiene, efficiency, and recycling. To address these challenges, Design Thinking, the Kano model, and the Analytic Hierarchy Process (AHP) were applied in the development of an innovative broom and dustpan set, tailored to users’ needs. A survey revealed that 70% of respondents were dissatisfied, highlighting compactibility, easy assembly, and improved storage as valued attributes. The Kano model classified storage, portability, and practicality as attractive attributes, while separation, hygiene, and usability were considered mandatory. The AHP method confirmed that separation, recycling, and hygiene are key priorities in the product design. Prototype testing and refinement demonstrated that combining these methodologies enabled a comprehensive evaluation, resulting in a functional, adaptable, and sustainable product. This design enhances waste management and hygiene in vending stalls and can be applied to other informal trade contexts, fostering more sustainable practices in urban environments.